2021
DOI: 10.1016/j.chest.2020.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Investigation of the Efficacy of Antimycobacterial Therapy in Chronic Pulmonary Sarcoidosis

Abstract: Background A Phase I, single-center investigation found that 8 weeks of antimycobacterial therapy improved sarcoidosis FVC. Safety and efficacy assessments have not been performed in a multicenter cohort. Research Question The objective of this study was to determine the safety and efficacy of antimycobacterial therapy on the physiological and immunologic end points of sarcoidosis. Study Design and Methods In a double-blind, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 34 publications
1
19
3
Order By: Relevance
“…While further work is needed to explore the long-term stability of remission in patients with previously recurrent sarcoidosis, sustained antigen tolerance is a plausible mechanism. In contrast to tolerance, findings from a Phase I preclinical sarcoidosis trial suggested that enhancing host immune responses may facilitate antigen clearance, lending hope for true long-term disease remission ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…While further work is needed to explore the long-term stability of remission in patients with previously recurrent sarcoidosis, sustained antigen tolerance is a plausible mechanism. In contrast to tolerance, findings from a Phase I preclinical sarcoidosis trial suggested that enhancing host immune responses may facilitate antigen clearance, lending hope for true long-term disease remission ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…As much as is possible, trial populations should be reflective of the populations affected by the disease of interest. Sarcoidosis occurs three times more commonly in African Americans and presents with disproportionate severity in patients of a lower socioeconomic status (SES) (40,42,45,103,104), yet most trial populations thus far have not been reflective of this racial prevalence of disease (105,106). Several studies show that African Americans are less likely to both qualify for and to participate in clinical trials due to several reasons such as mistrust in the system, lack of interest in clinical trials, fear and stigma associated with participation, and a perception that they may not be compliant with trial protocols (107)(108)(109)(110).…”
Section: Challenges Affecting Drug Trials and Drug Development In Sar...mentioning
confidence: 99%
“… 53 Antimycobacterial treatment (CLEAR regimen) for 4 months failed to demonstrate clinical or physiological improvement in chronic pulmonary sarcoidosis. 54 Repository corticotropin injection (RCI) was approved in the 1950s for sarcoidosis. Originally considered a steroid analog, RCI may have additional immunological properties and a steroid-sparing effect, although its action is currently limited.…”
Section: Treatmentsmentioning
confidence: 99%